The Isak Mosque and the Ismail Church: A Symbol of Muslim-Christian Cultural Interaction in East Alila, Ilawe Village, Alor - Ayu Apriany Benu (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This article aims to describe and analyze the views of the Ilawe village community regarding the existence of the Isak mosque and the Ismail church which can be a symbol of cultural interaction in Alor district. In writing this, I did not only provide the history of the Isak mosque and the Ismail church, but also the ways of dialogue between those religious communities in the place. Besides, it also describes how people establish their relationship and lives in harmony in various problems and debates occurred in other places. The interfaith dialogue which is built in the community is based on their day-to-day relationships. The research method used is a qualitative approach with a survey and interviews for the data collection. Both methods can encourage the author to look at how the Ilawe community comprehends the Isak mosque and the Ismail church. The existence of the Isak mosque and the Ismail church can also be a symbol of the cultural interaction of the people in Alor district. The research concludes that the Isak mosque and the Ismail church are symbols of cultural interaction in interfaith dialogue for people in Ilawe village and all communities in Alor district.